The study of the biological activities of Ziziphora clinopodioides - Ulikhanyan Greta; Galstyan Hasmik; Dumanyan Karine; Beglaryan Margarita; Poghosyan Gayane; Shekoyan Vladimir; Ananikyan Hrachya; Ananikyan Violeta; Goginyan Vigen; Ulikhanyan Ghukas; Chichoyan Naira; Taschyan Sona (Universidade de São Paulo, 2022)
Abstract The aim of the current study was to determine the chemical constituents of essential oil and to study the antibacterial and antioxidant activities of essential oil and the extracts obtained from the raw material of Ziziphora wild growing in the floras of Armenia and Artsakh cultivated in the hydroponic conditions. The essential oils were obtained by the method of hydro-distillation. The determination of the essential oil constituents were performed by the GC-MS method. Agar disk diffusion method was used to study the antimicrobial activity of essential oils. The antioxidant activity determination was carried out DPPH test by the spectrophotometric method, at the same time IC50 was determined. The highest values of the essential oils yield (1.25 ± 0.01%) and IC50 13.83±0.218(x10-5)g/l) were received for the plant cultivated in hydroponic conditions. For the first time in the above studied samples, by the method of GC-MS more than 70 components were revealed. The results of the study showed that essential oils of Ziziphora exhibit antimicrobial activity and the extracts revealed relatively expressed antioxidant activity. The study results show the future prospects of the use of Ziziphora not only as the source of flavonoids and essential oils, but also antimicrobial and antioxidant agents.